2019
DOI: 10.2147/jpr.s203553
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patterns of drug treatment in patients with osteoarthritis and chronic low back pain in Japan: a retrospective database study</p>

Abstract: Purpose: Musculoskeletal diseases, including osteoarthritis (OA) and low back pain (LBP), are the leading causes of years lived with disability, and are associated with lowered quality-of-life, lost productivity, and increased healthcare costs. However, information publicly available regarding the Japanese real-world usage of prescription medications is limited. This study aimed to describe the clinical characteristics of patients with OA and chronic LBP (CLBP), and to investigate the patterns of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 42 publications
9
42
1
1
Order By: Relevance
“…In contrast, a recent publication from Belgium [22] reported that NSAIDs were prescribed to 29.4% of knee OA patients in 2015, a relatively similar rate to our observation in Israel. We found that 22.9% of OA patients used opioids, similar to the rates observed in Sweden (23.7%) [23] and the US (27%) [31], but higher than the 10% reported in Belgium [22] and Japan [18]. Paracetamol was used by approximately 20% of the OA patients in our study, a similar rate to Japan [18] and Belgium [22], but much higher than in Korea [21].…”
Section: Analgesic Usesupporting
confidence: 84%
See 2 more Smart Citations
“…In contrast, a recent publication from Belgium [22] reported that NSAIDs were prescribed to 29.4% of knee OA patients in 2015, a relatively similar rate to our observation in Israel. We found that 22.9% of OA patients used opioids, similar to the rates observed in Sweden (23.7%) [23] and the US (27%) [31], but higher than the 10% reported in Belgium [22] and Japan [18]. Paracetamol was used by approximately 20% of the OA patients in our study, a similar rate to Japan [18] and Belgium [22], but much higher than in Korea [21].…”
Section: Analgesic Usesupporting
confidence: 84%
“…Despite the existence of several guidelines for the treatment of OA, the practical treatment of OA is not homogeneous in all countries. Our [18,21]. In contrast, a recent publication from Belgium [22] reported that NSAIDs were prescribed to 29.4% of knee OA patients in 2015, a relatively similar rate to our observation in Israel.…”
Section: Analgesic Usesupporting
confidence: 81%
See 1 more Smart Citation
“…М. Akazawa и соавт. [12], изучавшие применение обезболивающих средств у 118 996 пациентов с ОА с 2013 по 2017 г. по данным японского национального регистра, установили, что примерно 90% из них были назначены НПВП. С. Zeng и соавт.…”
Section: безрецептурные нестероидные противовоспалительные препараты unclassified
“…Surgical therapy, non-pharmacological therapy (exercise, gait aids, cognitive behavioral therapy, and self-management programs), and pharmacological therapy are available management options for treating pain associated with OA and CLBP [12][13][14][15]. An analysis using data from hospital-based administrative databases showed that approximately 90% of patients with chronic musculoskeletal pain were prescribed non-steroidal anti-inflammatory drugs (NSAIDs) in Japan [16]. Transdermal NSAID patches have demonstrated a superior safety profile over oral NSAIDs, and are recommended as first-line treatment for knee and hip OA by the Osteoarthritis Research Society International (OARSI) guidelines [13,14,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%